Amino acid derivatives as regulatory molecules: Mechanisms in plant growth and stress tolerance - Ning Ouyang; Wenjuan Hu; Jieqiong Meng; Bo Wang (Crop Journal)
Plants produce many amino acid derivatives (AADs). Some have been used by humans as medicines and nutrients, but many also act as phytochemical signals in plant growth and stress tolerance. The fluctuating ecological environment poses a constant challenge to plant growth and development, and also presents significant obstacles to agricultural productivity. Plant AADs hold substantial potential for agricultural applications to increase plant resilience against diverse biological and environmental pressures. In this review, we present recent advances in elucidating the biological roles of plant AADs in plant growth and stress tolerance and outline strategies for discovering novel AADs and their regulatory networks in crops. The review aims to gain new insights into the functional properties of AADs in regulating plant growth and stress responses, which provides a valuable foundation for developing innovative AAD-based strategies to improve crop performance and resilience facing the ever-changing environment in the future.